Inspecting Myth, Queer, and Contemporaneity in Devdutt Pattanaik’s selected stories from the work Shikhandiand Other Queer Tales They Don’t Tell You - et. al., Gayathry Sunil, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mythology plays an important role in the progression of society. It has a direct impact on the readers as well as civilization. Indian literature is diverse. It is a collectionof literature from otherlanguages such as Tamil, Marathi, Odiya, Bengali, Sanskrit, Hindi, Urdu, Malayalam, Gujarati, etc. All these writings somehow explore the merits and the demerits of a specific region’s decorum. Dr. Devdutt Pattanaik is a writer, illustrator, mythologist and lecturer, who is very much absorbed in transmitting the pertinence of past and mythology in the modern era. He uses mythology as a tool to estimate society. His work Shikhandi And Other Queer Tales They Don’t Tell You is a collection of short stories from different Indian mythologies that exposes queer elements. This paper attempts to make an analysis of queerness in today’s society with the support of Pattanaik’s this prominent work. Also, social issues like gender parity, feminism, patriarchy, queerness, etc. are vividly discussed with the aid of mythology. The book creates a broad spectrum for the reader with the kaleidoscopic eyes of Pattanaik.